Drug-based cancer therapy to overcome immune resistance by steering tumor evolution - Fernandez, Ariel (2019)
We argue that therapy must lead rather than follow vis-à-vis cancer evolution. Clinical experience suggests that the evading phenotype resulting from treatment can never be fully anticipated or eliminated when a single source of selection pressure is applied during treatment. Thus, therapy must steer cancer evolution and LIC may well become the underlying paradigm to overcome resistance in a therapeutic context where immune surveillance is maintained.